Roles of cytoskeletal proteins in the predatory life cycle of Bdellovibrio bacteriovorus - Fenton, Andrew Karl (2010)
Bdellovibrio bacteriovorus are small, predatory bacteria that grow within the periplasmic space of a host bacterium. Bdellovibrio has a biphasic life-cycle switching from a uni-nucleoid, growth-senescent ‘attack-phase’ to a novel, multi-nucleoid filamentous ‘growth-phase’, which elongates and divides, growing saprophytically within the periplasmic space of their prey. Little is known to date about Bdellovibrio developmental processes and cell division within this periplasmic niche.